Metabolic biomarkers in patients with type 2 diabetes mellitus and heart failure with preserved ejection fraction - T. S. Sveklina; S. B. Shustov; S. N. Kolyubayeva; A. N. Kuchmin; V. A. Kozlov; E. V. Smirnova; A. V. Zharkov (Сахарный диабет)
BACKGROUND: Half of all patients with chronic heart failure (CHF) have preserved ejection fraction (CHF-nEF). The drug’s use effective for treatment of CHF with reduced ejection fraction (CHF-nFV) reduces the hospitalization incidence but does not affect the cardiovascular incidence or overall mortality in patients with CHF-nFV. Finding differences between CSN-SFV and CSN-nFV biomarkers is a pressing scientific problem.AIM: To study the metabolic disorders biomarkers intergenic relationships, myocardial damage, and to evaluate their role in the CHF development in patients with DM2.MATERIALS AND METHODS: We studied the lipid and carbohydrate metabolism disorder genes polymorphisms frequencies in patients with CHF-CFV and DM2 (48 patients), CHF-NFV and DM2 (46) and patients with metabolic syndrome (MS) without CHF (68), mean age of patients was 69,7±5,3 yo. DNA was isolated from venous blood according to the manufacturer’s methodology. Gene polymorphisms were determined by real time PCR. The studied polymorphisms correlations with clinical and laboratory data and associations between clinical and laboratory tests were identified by regression analysis.RESULTS: In the control group, PPARG, APOC3 C3238G rs5128, LIPC -250 G>A rs2070895, APOA1 G-75A rs670, FABP2 Ala54Thr G>A rs1799883, ADRB2 5318 C>G rs1042714 genes polymorphisms, along with co-dependent ADRB3, FTO, FABP2 genes polymorphic form a gene network regulating plasma concentrations of LDL, uric acid and CAD. Gene polymorphisms have been found to be associated with clinical and/or laboratory parameters in patients with CHF-CFV: PPARGC1AGly482Ser G>A rs8192678 with CAD; PPARGT-2821C rs12497191 with glycated hemoglobin level; FTO A>T rs9939609 (α-ketoglutarate dependent dioxygenase gene) with waist circumference; LEPR A>G rs1137101 (leptin receptor gene) with MAP. The following polymorphisms were found to be associated in patients with CHF-nFV: LIPC-250 G>A rs2070895 (liver triglyceride lipase gene) with MAP; PPARGC1A Gly482Ser G>A rs8192678 with MAP; FTO A>T rs9939609 with waist volume.CONCLUSIONS: From the study results, it is evident that patients with DM2 having CHF with different PV differ significantly among themselves by the presence of polymorphic genes prone to network interactions. The greatest number of such interactions is observed in the group of CHF-sFV, which determines a more complex course of this variant of CHF than in patients with CHF-nFV.